Study of the working body mechanism in forging-and-stamping equipment - K. O. Kobzev (Advanced Engineering Research)
Introduction. The synthesized basic diagram of the frictional contact of solids in forging-and-stamping machines is considered. The possibility of obtaining the maximum load characteristics of the frictional contact within the variation interval of the friction factor is determined. The following two possibilities of frictional contact forces are indicated: they will be equal at the boundaries of the specified interval if there is maximum balance; they achieve the greatest stability under these conditions.Materials and Methods. When the angle value changes, the position of the maximum point changes. This causes violation of the friction forces balance at the boundaries of the variation interval of the friction factor. In this case, the accuracy coefficient should be determined by the ratio of the maximum of function to the least boundary value. Doing this requires establishing trends of changing the boundary function values associated with the angle variation. To solve this problem, a new value of the pressure angle tangent was presented as a product of the coefficient of variation by the base value of the angle tangent.Research Results. The results show high stability of the friction force under slipping of the frictional contact (FC) bodies. However, at large values of the pressure angle of sensing elements of the transducer, the maximum friction force can be for a short moment proportional to the current value of the friction factor.Discussion and Conclusions. The upgraded FC basic diagram enables to theoretically obtain very high stability of the friction force. The FC should not vanish within the variation interval of the friction factor of the output parameter of the basic friction group (BFG) and at the maximum of function of the FC load capacity. A necessary condition for that is the transfer of full capacity of the additional friction group (AFG) by the sensing elements.